Evaluating Implicit Measures to Improve Web Search - Fox, Steve; Karnawat, Kuldeep; Mydland, Mark; Dumais, Susan, Thomas White (ACM:TOIS, 2005)
Of growing interest in the area of improving the search experience is the collection of implicit user behavior measures (implicit measures) as indications of user interest and user satisfaction. Rather than having to submit explicit user feedback, which can be costly in time and resources and alter the pattern of use within the search experience, some research has explored the collection of implicit measures as an efﬁcient and useful alternative to collecting explicit measure of interest from users. This research article describes a recent study with two main objectives. The ﬁrst was to test whether there is an association between explicit ratings of user satisfaction and implicit measures of user interest. The second was to understand what implicit measures were most strongly associated with user satisfaction. The domain of interest was Web search. We developed an instrumented browser to collect a variety of measures of user activity and also to ask for explicit judgments of the relevance of individual pages visited and entire search sessions. The data was collected in a workplace setting to improve the generalizability of the results. Results were analyzed using traditional methods (e.g., Bayesian modeling and decision trees) as well as a new usage behavior pattern analysis (“gene analysis”). We found that there was an association between implicit measures of user activity and the user’s explicit satisfaction ratings. The best models for individual pages combined clickthrough, time spent on the search result page, and how a user exited a result or ended a search session(exit type/end action). Behavioral patterns (through the gene analysis) can also be used to predict user satisfaction for search sessions.